Implementation of the Disclosure Principle in Submitting Evidence in Civil Lawsuits Through e-Court in the Class 1 A District Court Medan and Class 1 A District Court Lubuk Pakam - Mulhadi, Mulhadi; Barus, Utary Maharany; Harianto, Dedi; Sembiring, Idha Aprilyana; Wau, Hilbertus Sumplisius M. (JURNAL MERCATORIA, 2024)
This article aims to determine the implementation of the principle of disclosure in submitting evidence in civil lawsuits through e-Court in the district court, by taking the location of research in the Class 1 A District Court Medan and Class 1 A District Court Lubuk Pakam. Technological advances have provided convenience in public services, including electronic case resolution services in district courts with the introduction of e-Court. The research methods used are the type of normative juridical research supported by field research, the approach methods used are statutory approaches and conceptual approaches, secondary data sources and primary data, technical data collection literature research and field research, qualitative data analysis and deductive conclusions. This study concludes that the electronic justice system (e-Court) in the Medan Class 1 A District Court and Lubuk Pakam Class 1 A Court provides convenience to the parties concerned and their legal representatives to submit evidence in civil lawsuits, but regarding the implementation of the principle of disclosure, the information obtained regarding evidence is only limited to information on letter evidence that enters the Court Information Tracing System which is still of doubtful authenticity without direct mail check.